Designing unmanned systems with greater autonomy : using a federated, partially open systems architecture approach - Gonzales, Daniel R.; Harting, Sarah J.; Rand eBooks (Santa Monica, CA : RAND, 2014)
Current unmanned systems (UxSs) use different communication systems and have limited autonomy, which can contribute to interoperability problems and limit the degree to which information collected by these systems can be shared with warfighters and other UxSs operating in the same area. UxSs may also face survivability and mission effectiveness challenges when they operate in contested environments or against adversaries with significant electronic or cyber warfare capabilities. Improving UxS autonomy can address these challenges. This report identifies a partially open systems architecture (POSA) approach that can improve system interoperability and autonomy. A POSA reference model is proposed for unmanned aircraft vehicles that can enable new autonomous capability modules to be inserted into the system.
Introduction -- Expanding the UxS Mission Space -- UAS Interoperability Initiatives Led by the Office of the Secretary of Defense -- Unmanned System Autonomy: Limitations and Opportunities -- UxS Architecture Developments -- Conclusions.
"RAND National Defense Research Institute."
"Prepared for the Office of the Secretary of Defense."
"This research was ... conducted within the Acquisition and Technology Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 61-65).
Also available on the internet via WWW in PDF format.
Description based on print resource.
Keywords: Vehicles, Remotely piloted; Automatic control; Robotics; Communications, Military; Electronic books